Disaster Risk Financing and Contingent Credit : A Dynamic Analysis - Clarke, Daniel; Mahul, Olivier (2012)
This paper aims to assist policy makers interested in establishing or strengthening financial strategies to increase the financial response capacity of developing country governments in the aftermath of natural disasters, while protecting their long-term fiscal balance. Contingent credit is shown to increase the ability of governments to self-insure by relaxing their short-term liquidity constraints. In many situations, contingent credit is most effectively used to facilitate risk retention for middle layers, with reserves used for bottom layers and risk transfer (for example, reinsurance) for top layers. Discussions with governments on the optimal use of contingent credit instruments as part of a sovereign catastrophe risk financing strategy can be guided by the output of a dynamic financial analysis model specifically developed to allow for the provision of contingent credit, in addition to reserves and/or reinsurance. This model is illustrated with three country case studies: agricultural production risks in India; tropical cyclone risk in Fiji; and earthquake risk in Costa Rica.